Impact of Systolic Blood Pressure Trajectories and Variability on Unexplained Early Neurological Deterioration Post‐Endovascular Treatment in Acute Ischemic Stroke Patients - Xuxuan Gao; Qiheng Wu; Yu Ma; Yueran Ren; Jiaying Chen; Xiaofei Lin; Lianghao Ye; Wei Song; Jiajia Zhu; Jia Yin (The Journal of Clinical Hypertension)
ABSTRACT Early neurological deterioration (END) following endovascular treatment (EVT) in acute ischemic stroke (AIS) patients is associated with poor long‐term outcomes. Although unstable systolic blood pressure (SBP) after EVT is recognized as a risk factor for END, it remains unclear whether this association persists after excluding identifiable causes of END. In this prospective, observational cohort study, AIS patients who underwent EVT within 24 h of stroke onset were included. Invasive arterial blood pressure (BP) monitoring recorded hourly BP readings during the first 24 h post‐EVT. Unexplained END was defined as an increase of ≥4 points in the National Institutes of Health Stroke Scale score 24 h after EVT without any identifiable cause. Two distinct SBP trajectories—high and low—were identified within 24 h post‐EVT. The high‐trajectory group, characterized by elevated mean SBP and increased SBP variability (SBPV), exhibited a significantly higher incidence of unexplained END (odds ratio [OR] = 3.28, p < 0.01). SBPV alone was an independent risk factor for unexplained END (OR = 1.11, p < 0.05). Moreover, patients with both higher mean SBP and increased SBPV had a markedly greater risk of unexplained END (OR = 13.79, p < 0.05). Notably, the harmful threshold for SBPV was lower during nighttime compared to daytime. These findings suggest that increased SBPV, particularly when combined with elevated mean SBP, significantly heightens the risk of unexplained END post‐EVT. Therefore, comprehensive post‐EVT blood pressure management should address both absolute BP levels and BPV, with particular emphasis on nighttime monitoring, to optimize early neurological recovery.